Introduction to Biologically Inspired Robotics - Liu, Yunhui; Sun, Dong (Biologically Inspired, 2012)
This chapter gives a brief introduction to biologically inspired robotics. We will discuss what biological inspired robotics is, its major topics, and brief history. Some well-known biologically inspired robots and technology will be also introduced. This chapter provides a brief introduction to biologically inspired robotics. It discusses what biological inspired robotics is, its major topics, and brief history. Biologically inspired robotics is an interdisciplinary subject of robotics and biology and consists of mainly two broad areas: biomimetics and bio-robotic modeling/analysis. Designing mechanisms for robots that mimic the motion of animals and other living creatures is one of the core problems in biologically inspired robotics. Bio-robotic modeling/analysis is the application of robotic models and principles to address biological issues such as recognition processes of the human brain, behaviors of animals and insects. Humans have tried to create mechanical systems that mimic the behaviors of animals and other living creatures for a long time. The behaviors of animals and other living creatures inspire the development of new ideas for controlling the motion or behaviors of robots. Behavior control was originally developed to solve the problem of motion control for mobile robots.